Root growth characteristics and antioxidant system of Suaeda salsa in response to the short-term nitrogen and phosphorus addition in the Yellow River Delta - Ma, Jinzhao; Xin, Xin; Cao, Yu; Zhao, Liying; Zhang, Zehao; Zhang, Dongjie; Fu, Zhanyong; Sun, Jingkuan (Frontiers in Plant Science, 2024)
Human activities have increased nitrogen (N) and phosphorus (P) inputs to the Yellow River Delta and the supply level of N and P affects plant growth as well as ecosystem structure and function directly. However, the root growth, stoichiometry, and antioxidant system of plants in response to N and P additions, especially for herbaceous halophyte in the Yellow River Delta (YRD), remain unknown. A field experiment with N addition (0, 5, 15, and 45 g N m -2 yr -1 , respectively) as the main plot, and P addition (0 and 1 g N m -2 yr -1 , respectively) as the subplot, was carried out with a split-plot design to investigate the effects on the root morphology, stoichiometry, and antioxidant system of Suaeda salsa. The results showed that N addition significantly increased the above-ground and root biomass as well as shoot-root ratio of S. salsa, which had a significant interaction with P addition. The highest biomass was found in the treatment with 45 g N m -2 yr -1 combined with P addition. N addition significantly increased TN content and decreased C:N ratio of root, while P addition significantly increased TP content and decreased C:P ratio. The main root length (MRL), total root length (TRL), specific root length (SRL), and root tissue density (RTD) of S. salsa root were significantly affected by N addition and P addition, as well as their interaction. The treatments with or without P addition at the 45 g N m -2 yr -1 of N addition significantly increased the superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) activities and soluble protein content of roots, decreased malondialdehyde (MDA) content. And there was a significant interaction between the N and P addition on SOD activity. Therefore, N and P additions could improve the growth of S. salsa by altering the root morphology, increasing the root nutrient content, and stimulating antioxidant system.